The Impact of internet usage for academic purposes on nursing students’ achievement - Jamaludin, Thandar Soe Sumaiyah; Awang Kechik, Nurulhusnaa; Mei Chan, Chong (Scholars Academic & Scientific Publishers, 2017)
The growth of the Internet is one of the advancements in technologies that change our life in many ways. Internet can be used as communication tools, entertainment and a medium to increase the knowledge of university students. As nursing students, they must be equipped with the correct knowledge about medicines and care so that they will achieve better marks in their examination as well as able to provide better nursing care to patients. In light of that, this study was carried to analyze the impact of usages of internet for academic purposes on nursing students’ academic achievements. This was a cross-sectional survey by applying of purposive sampling method carried out among 127 undergraduate nursing students from year 2 until year 4. The self-administered questionnaire was distributed to the studied participants and it was collected by the researcher. Majority of participants were females and their age were 23 years old. The result showed there was no significant relationship between the students’ usage of internet for their academic purposes with their academic achievement in Chi square test. However, there was association between genders and participants’ academic performance with p value of less than 0.05. From this finding, it is advisable for the students to use the internet effectively for their studies and future career benefit. The lecturers/educators can use this finding to guide their students so that they use the reliable websites to make their studies more interactive and interesting. Keywords: Impact, Internet usage, Academic achievement, Nursing students.